Keeping Millennials in the Public Sector: Comparing Turnover Intentions of Millennial and Older Generation Civil Servants. - Lee, Young-joo; Hwang, Hyunseok; Lim, Sungdae; Yoon, Taewon (Public Personnel Management, 2026)
This study examines and compares how the perceptions of individual- and organization-level work environments relate to millennial and older generation civil servants' turnover intention, using the 2021 survey of South Korean government employees. Both split-sample OLS and moderated multiple regression models were estimated, and the findings reveal significant differences between the two generational groups. Most of all, perceived pay competitiveness, task meaningfulness, and innovative organizational culture are more strongly related to turnover intentions among millennial civil servants than among their predecessors. The findings suggest that addressing millennial civil servants' retention should take a distinctive approach from the traditional public sector retention strategies. This study presents policy recommendations for government human resources management.